Mental competencies and executive functions in Austrian junior elite alpine skiers and soccer players - Finkenzeller, T.; Würth, S.; Amesberger, G. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Alpine skiing and soccer are very attractive sports for adolescent Austrian girls to be practiced on high-performance level. These focus groups, however, represent an under-researched area. It is assumed that female adolescent athletes of individual and team sport will differ in mental competencies. Subsequently, different sport psychological topics could be of interest to be encouraged in this sensitive development phase. Furthermore, executive functioning seems to be a very promising indicator of expertise in soccer (Vestberg et al., 2012), and is considered to differentiate between soccer players and alpine skiers due to different cognitive demands of the sports. Aim of this exploratory study was to compare i) mental skills of female adolescent elite alpine skiers and soccer players and to ii) evaluate executive functioning of alpine skiers and soccer players in comparison to a female control group not taking part in competitive sport.